Answer:
x = - 5
Step-by-step explanation:
Given h(x) = 6x - 2 and h(x)= - 32, then equate the right sides, that is
6x - 2 = - 32 ( add 2 to both sides )
6x = - 30 ( divide both sides by 6 )
x = - 5
Answer:
a^2-12a+36
Step-by-step explanation:
;)
Answer:
D: y= -2x -1
Step-by-step explanation:
The line crosses the y axis at -1 and using the "rise over run" phrase you can tell that the next point is 2 up and 1 over (2/1 =2) the line is also negative because it moves down from left to right. Therefore, y= -2 -1
x² + 3x: common factor is x
1x + 3: common factor is 1
From here I do not understand how you get to the answer which I do know is (x + 1) • (x + 3).
None of the explanations out there give detail to this step. I don’t understand how adding those two groups up (while pulling out common factors) will give you (x + 1) • (x + 3)!
I would hugely appreciate any help on this! Thank you :)